Advances in Foot-and-Mouth Disease Virus Proteins Regulating Host Innate Immunity - Peng, Jiangling; Yi, Jiamin; Yang, Wenping; Ren, Jingjing; Wen, Yuan; Zheng, Haixue; Li, Dan (Frontiers in Microbiology, 2020)
Foot-and-mouth disease (FMD) is a highly contagious disease that affects cloven-hoofed animals such as pigs, cattle, and sheep. The disease is caused by the foot-and-mouth disease virus (FMDV) which has a non-enveloped virion with icosahedral symmetry that encapsulates a positive-sense, single-stranded RNA genome of ∼8.4 kb. FMDV infection causes obvious immunosuppressive effects on the host. In recent years, studies on the immunosuppressive mechanism of FMDV have become a popular topic. In addition, studies have shown that many FMDV proteins are involved in the regulation of host innate immunity and have revealed mechanisms by which FMDV proteins mediate host innate immunity. In this review, advances in studies on the mechanisms of interaction between FMDV proteins and host innate immunity are summarized to provide a comprehensive understanding of FMDV pathogenesis and the theoretical basis for FMD prevention and control.